Multidisciplinary analysis of invasive meningococcal disease as a framework for continuous quality and safety improvement in regional Australia. Issue 1 (7th February 2018) - Taylor, Kathryn A; Durrheim, David N; Merritt, Tony; Massey, Peter; Ferguson, John; Ryan, Nick; Hullick, Carolyn
Abstract : Background: System factors in a regional Australian health district contributed to avoidable care deviations from invasive meningococcal disease (IMD) management guidelines. Traditional root cause analysis (RCA) is not well-suited to IMD, focusing on individual cases rather than system improvements. As IMD requires complex care across healthcare silos, it presents an opportunity to explore and address system-based patient safety issues. Context: Baseline assessment of IMD cases (2005–2006) identified inadequate triage, lack of senior clinician review, inconsistent vital sign recording and laboratory delays as common issues, resulting in antibiotic administration delays and inappropriate or premature discharge. Methods: Clinical governance, in partnership with clinical and public health services, established a multidisciplinary Meningococcal Reference Group (MRG) to routinely review management of all IMD cases. The MRG comprised representatives from primary care, acute care, public health, laboratory medicine and clinical governance. Baseline data were compared with two subsequent evaluation points (2011–2012 and 2013–2015). Interventions: Phase I involved multidisciplinary process mapping and development of a standardised audit tool from national IMD management guidelines. Phase II involved formalisation of group processes and advocacy for operational change. Phase III focused on dissemination of findings to clinicians and managers. Results: Greatest care improvements were observed in the final evaluation. Median antibiotic delay decreased from 72 to 42 min and proportion of cases triaged appropriately improved from 38% to 75% between 2013 and 2015. Increasing fatal outcomes were attributed to the emergence of more virulent meningococcal serotypes. Conclusions: The MRG was a key mechanism for identifying system gaps, advocating for change and enhancing communication and coordination across services. Employing IMD case review as a focus for district-level process reflection presents an innovative patient safety approach, combining the strengths of prospective hazard analysis with more traditional RCA methodologies.